Pengaruh Penempatan dan Perilaku Kerja Terhadap Kinerja Pegawai Badan Lingkungan Hidup Kabupaten Rokan Hulu - Kartika Indra Bella; Susi Hendriani; Henni Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine how the variables influence Placement and Work Behavior simultaneously and partially on the Environment Agency employee performance Rokan Hulu. The samples in this study were as many as 60 people, the determination of the number of samples based on census method. Analysis of the data used is descriptive analysis, but it is also a quantitative analysis that is using multiple linear regression with SPSS version 18. From the results of the testing that has been done, simultaneous regression test ( F-test ) showed that the Work Placement and Behavior simultaneously jointly significant effect on employee performance. Partial Test Results (t test ) showed that the variable placement of partially significant effect on employee performance, and variables Work Behavior partially significant effect on employee performance. The magnitude of the effect caused by these three variables together against the dependent variable was 70.9 %, this means that the variable placement, and work behavior, jointly affect the performance of employees. While 29.1 %, affected by other factors that are not involved in this study.Keywords: Performance , Placement , Job Behavior